Improving Student's Vocabulary Mastery Through Guessing Picture : A Classroom Action Research At The Fifth Grade Of SD N 1 Dukuh Banyudono Boyolali In 2012/2013 Academic Year - Shidiq, Mohammad Sholeh; , Aryati Prasetyarini, S. Pd., M. Pd; , Dra. Siti Zuhriah Ariatmi, M.Hum (2013)
This research aims at (1) describing the application of Guessing Picture in teaching and vocabulary process, (2) describing the improvement student's vocabulary mastery through Guessing Picture. This research was implemented in SD N I Dukuh Banyudono Boyolali at the fifth class, using action research. The methods of collecting the data are observation, interview, analyzing document assumps, and test. The researcher, that Guessing Picture can improve vocabulary mastery. To analyze the data, the researcher compared the results of each cycle and posttests by using descriptive comparative and critical analytic technique. The action was done in two cycles with four steps each. The result, of the research can be described as: (1) The implementat on of Guessing Picture can improve the students interest,motivation and involvement in the learning process;(2) The implementation of Guessing Picture can improve the students' vocabulary easy mastery/achievement of the test conducted after each cycles, the Achievement by two steps: oral and written. after the first cycle and two cycles in implementing Guessing Picture in teaching vocabulary, the students become able to interest and cooperative in learning vocabulary. It can be seen from the result of the students' activities during the action and the students' vocabulary achievement. The mean of pre-test is 59,03, post-test 93,61 and the improvement result of the implementation is 28,50%. Most of the students said that they love this method. Thus, it makes them can master vocabulary correctly. The students can do the post-test better than pre-test. So, using Guessing Picture is successful to improve the students' vocabulary mastery.